The Development of Preschoolers' Living Kinds Concept: A Longitudinal Study. Issue 4 (19th December 2016) - Margett‐Jordan, Tessa; Falcon, Rachael G.; Witherington, David C.
Abstract : Given limitations in the integrative scope of past research, basic questions about the organization and development of preschoolers' living kinds concept remain open to debate. This study was designed to address past limitations through use of a longitudinal design, extensive stimulus set, and alternate indices of understanding. Thirty‐five English‐speaking 3‐year‐olds from middle‐class families in Albuquerque, NM participated in four testing sessions over 1 year. Indices of understanding included statements that preschoolers generated about various living and nonliving objects, biological properties they attributed to the objects, and their characterization of objects as "alive" or not. Results reveal a multifaceted picture of developmental change in preschoolers' living kinds concept involving both the construction and elaboration of a core biological understanding.